OP0136 Sex Differences in Gout Characteristics: Tailoring Care for Women and Men. (10th June 2014) - Harrold, L.R.; Etzel, C.J.; Gibofsky, A.; Kremer, J.M.; Pillinger, M.H.; Saag, K.G.; Schlesinger, N.; Terkeltaub, R.; Cox, V.; Greenberg, J.D.
Abstract : Objectives: Using a national registry of gout patients cared for by rheumatologists, we sought to characterize the differences between women and men with gout, in terms of predisposing factors, comorbid conditions, and treatments, in order to tailor and improve gout care to both sexes. Methods: Rheumatologists participating in the Consortium of Rheumatology Researchers of North America (CORRONA) registry agreed to enroll their gout patients regardless of gender, disease severity, disease activity or medication use. All patients enrolled between 11/1/12 and 12/11/13 were included in the current study. Data gathered from patients and their rheumatologists at study enrollment included demographics, predisposing factors (comorbid conditions, medications, diet), gout disease characteristics, current treatments, and physical exam findings. Results: Fifty-four rheumatologists enrolled 239 women and 928 men with gout. Women were older (71 vs. 61 years, p<0.001), more commonly nonwhite (18% vs. 12%, p=0.01), heavier (body mass index 34 vs. 32, p=0.001) and more commonly had hypertension (77% vs. 57%, p<0.001), diabetes (28% vs. 17%, p<0.001) and renal disease (25% vs. 14%, p<0.001). Women had a shorter duration of gout (6 vs. 11 years, p<0.001) and were less likely to have a crystal-proven diagnosis (26% vs. 35%, p=0.01). Medication risk factors for gout (e.g., diuretics), were more common in women (49% vs. 22%, p<0.001), while dietary risk factors were more frequent in men (intake of beer, hard liquor, beef and pork, all p<0.05). Women and men had similar clinical features in terms of acute gout presentation (podagra, oligoarthritis, etc.) when initially diagnosed with gout, and gouty arthritis (tophi, joint deformity), as well as average number of flares, but women reported more frequent disability (12 days vs. 7 days annually, p=0.001). Women were more likely to have contraindications to treatment with NSAIDs (31% vs. 21%, p=0.002) or colchicine (13% vs. 6%, p=0.001). Urate-lowering therapy in patients with tophi or active disease (≥2 flares/year) was prescribed in 78% of women and 84% of men (p=0.07). Conclusions: Women with gout more frequently were receiving predisposing medications, and had gout-associated comorbidities and/or contraindications to NSAIDs and colchicine, while men more commonly had dietary risk factors. Physicians should be aware of these differences, in order to tailor their treatment recommendations, to ensure all patients achieve optimal disease control. Acknowledgements: This study is sponsored by CORRONA. Initial funding for the CORRONA Gout registry was provided by Savient Pharmaceuticals, Inc. In the last two years, AbbVie, Amgen, AstraZeneca, Genentech, Horizon Pharma, Lilly, Novartis, Pfizer, Savient, Vertex, and UCB have supported CORRONA through contracted subscriptions. Disclosure of Interest: L. Harrold Grant/research support: Takeda and AstraZeneca, Consultant for: CORRONA, Inc., C. Etzel Employee of: CORRONA, Inc., A. Gibofsky Shareholder of: AbbVie, Amgen, BMS, GlaxoSmithKline, Johnson&Johnson, Pfizer, Roche (Genentech), Consultant for: AbbVie, Amgen, AstraZeneca, Celgene, Horizon, Iroko, Pfizer, Roche (Genentech), UCB, Takeda, Antares, Speakers bureau: Abbvie, Amgen, Pfizer, Roche (Genentech), UCB, J. Kremer Shareholder of: CORRONA, Inc., Employee of: CORRONA, Inc., M. Pillinger Grant/research support: Takeda, Savient, K. Saag Grant/research support: Takeda, Ardea, Consultant for: Takeda, Ardea, N. Schlesinger Grant/research support: Novartis, Consultant for: Novartis, Sobi, Speakers bureau: Novartis, Takeda, Savient, R. Terkeltaub Grant/research support: VA Research Service, Consultant for: Takeda, Savient, ARDEA, BioCryst, Novartis, Regeneron, Sobi, Pfizer, AbbVie, V. Cox Employee of: CORRONA, Inc., J. Greenberg Shareholder of: CORRONA, Inc., Consultant for: AstraZeneca and Pfizer, Employee of: CORRONA, Inc. DOI: 10.1136/annrheumdis-2014-eular.2486